COMPARATIVE EFFICACY AND SAFETY OF NEW ORAL ANTICOAGULANTS - V. A. Sulimov; D. A. Napalkov; A. A. Sokolova (Столичная издательская компания, 2015)
Indirect comparisons of new oral anticoagulants are performed with focus on their safety. Apixaban, an oral inhibitor of Xa factor, nowadays can be considered as a drug with very good safety profile according to randomized trials results and performed indirect comparisons.